Formulação, circulação e funcionamento discursivo da fotomontagem no facebook na des-estabilização de imagens de Dilma Rousseff como sujeito-político - Nezo, Ronaldo (2016)
This research has as investigated object the formulation, circulation and discursive functioning of the photomontage on Facebook in the de-stabilization of Dilma Rousseff's images as a political subject. For this purpose, are observed photomontages about Dilma in circulation during the period of the election campaign for the 2014 Republic Presidency, more specifically in the months of September and October. The presidential contest occurred between nine candidates, with, among them, was Dilma Rousseff, candidate for reelection by the Partido dos Trabalhadores (PT), which has been in power for twelve years. Considering the probable specificities of the election race, it pressupposed that Dilma and the PT government would be under attacks by the opponents and that social networks could participate in the de-construction of their application process. Faced with this, it was aimed to analyze the discursive functioning of photomontages that circulated on Facebook about the candidate Dilma Rousseff, during the 2014 presidential elections, observing, in the formulation-circulation encounter, the meaning effects originated from this functioning in the sustaining of the political subject image. Specifically, were raised conceptual notions about photomontage which allowed to promote a displacement of meanings from/between areas, understanding it as a discourse in its constitution, formulation and circulation; it sought to know the material specificity of Facebook as the photomontage discursive space of circulation and its participation in the meanings constitution of this visual-verbal materiality; finally, it has been described and interpreted, in the photomontage, the game of discursive elements which have been set on the scene in the production of the effects of truth and reality which introduced images of the political subject Dilma Rousseff, during the campaign for reelection. Having as theoretical and methodological reference the materialistic French Discourse Analysis, perspective of Michel Pêcheux, and its developments in Brazil, and considering the photomontage, in its discursive specificity, as a discourse about (which tells about, although it has its own specificity in constitution by the joke), which is put into circulation on Facebook, it sought to answer in what way the photomontage des-stabilized truth and reality meanings as the candidate Dilma Rousseff, during the period of the campaign for the 2014 presidential re-election. In the construction of analytical corpus, at around photomontages, it started by the notion of clipping by Orlandi (1984; 2000). Along the route, two central regularities were observed: "effect of reality", by showing scenes and facts which, in the imaginary, present themselves as if they were the reality itself; "effect of reality revelation", when the photomontages, easily identifiable in their own composition of visual images, (are) produce (in) a game of humor. This allowed to identify, in photomontages, the functioning of joke notions, developed by Freud (1996), and of rumor, tabled by Orlandi (2008), and the functioning of imaginary formations which makes to emerge in photomontages effects of truth and reality which culminate with the image negativization of the president and candidate for reelection, Dilma Rousseff, also of the former president Lula and the PT government, by meanings of corruption, arrogance, unpreparedness, lie, among others. That way, in the destabilization of the subject Dilma, linked to Lula and the PT, in which it destabilized the image of the political subject Dilma, candidate for reelection, and of her party, it stabilized an forged image in which the president-candidate and the PT were, imaginarily, interdicted in the Brazilian political landscape.